I.i.2.c Minutes, - Labour Party (Ireland) (1970)
Minutes of the Administrative Council which took place on 24 Jan 1970 principally concerning: adoption of resolutions to be proposed by the Administrative Council to Party conference 1970; Dublin South West constituency council; and East Limerick constituency council. Minutes signed by Dan Browne, Party Chair, and Brendan Halligan, General Secretary. (2 pp)